AA. Asriadi, Firmansyah, Nailah Analisis Pengembangan Usahatani Cabai Rawit Terhadap Peningkatan Produksi Melalui Varietas Di Kecamatan Galesong Kabupaten Takalar: Analisis Pengembangan Usahatani Cabai Rawit Terhadap Peningkatan Produksi Melalui Varietas Di Kecamatan Galesong Kabupaten Takalar - Firmansyah; Husain, Nailah; Asriadi, Andi Amran (Universitas Medan Area, 2025)
One of the agricultural sub-sectors that is very important in everyday life is horticultural crops. One of the horticultural crop commodities that are always needed by the people of Indonesia is cayenne pepper. This study aims to analyze the elasticity of cayenne pepper production and the level of production, income and feasibility of cayenne pepper farming based on two varieties in Galesong District, Takalar Regency. The research took place in Galesong District, Takalar Regency. The research location was determined by purposive sampling, on the grounds that farmers at the location regularly carry out cayenne pepper farming and there is an increase in production and income. The number of farmer samples was 66 respondents. Analysis of research data using production, income, feasibility and regression of scale comparison of cayenne pepper varieties. The results showed that the maruki variety had a production elasticity (EP) value of 1.254 and the bhaskara variety with a production elasticity (EP) value of 1.271, so that the situation was included in the return to scale increased along with the value of Ep> 1. This happens when the addition of inputs will produce additional production of a greater proportion. The feasibility level of the R / C ratio of cayenne pepper maruki variety is 2.34 while the R / C ratio value of cayenne pepper bhaskara variety is 2.27, thus the R / C Ratio value of cayenne pepper maruki and bhaskara varieties is said to be feasible because the value is > 1.